2017
DOI: 10.7759/cureus.1102
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Diagnosis of Scabies Using a Simple Saline Mount: A Clinical Microbiologist's Report

Abstract: Scabies is a skin condition caused by infestation of the mite Sarcoptes scabiei. Sarcoptes scabiei var. hominis is an arthropod member belonging to the order Acarina. Scabies is present throughout the world and is prevalent in all age groups, mostly involving people frequently in contact with animals, children, women, and elderly people. Predisposing factors for scabies include individuals with immunosuppressive conditions and people residing under low socioeconomic conditions. Skin lesions that occur during m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…There are few case reports that report concurrent leukemic involvement of the skin and crusted scabies [7,8]. Treatment of scabies resulted in the resolution of the skin lesions [7].…”
Section: Discussionmentioning
confidence: 99%
“…There are few case reports that report concurrent leukemic involvement of the skin and crusted scabies [7,8]. Treatment of scabies resulted in the resolution of the skin lesions [7].…”
Section: Discussionmentioning
confidence: 99%
“…The samples were analyzed and sent to a private laboratory in Guayaquil (Diagnovet, Guayaquil) for confirmation. Mites of the Sarcoptidae family were rinsed with 2% potassium hydroxide and observed under a binocular microscope to identify the parasite (Kandi, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…It was also suggested that routine saline mount can be employed for all cases that are examined for fungus, since KOH can kill the mites or immobilize them and a coinfection can be missed. 13…”
Section: Saline Mountmentioning
confidence: 99%